Building a European Partnership for next generation, systems‐based Environmental Risk Assessment (PERA): Final Roadmap Report. Issue 8 (11th August 2022) - Sousa, José Paulo; Aldrich, Annette; Axelman, Johan; Backhaus, Thomas; Brendel, Stephan; Dorronsoro, Begoña; Duquesne, Sabine; Focks, Andreas; Holz, Sheila; Knillmann, Saskia; Pieper, Silvia; Schmied‐Tobies, Maria; et al.
Abstract: The European Partnership for next generation, systems‐based Environmental Risk Assessment (PERA) is a strategic initiative launched by the European Food Safety Authority (EFSA). This initiative is in response to the recognition that the current ERA paradigm has "fallen out of step with scientific knowledge and progress" and the new policy and societal ambitions e.g. the EU Green Deal strategy to better safeguard the environment. As part of the initiative, EFSA commissioned the development of a roadmap to facilitate a transition to an integrated and cross‐sectoral environmental risk assessment (ERA) approach. The PERA systems‐based approach aims to connect relevant partners from various sectors across regulatory silos, promotes and facilitates the sharing of data and expertise, and improves efficiency and transparency of the risk assessment process. In this External Scientific Report, we present the PERA roadmap that comprises of a problem description (current state), a vision (future state) and a series of steps to move towards the vision (transition process). The PERA roadmap was developed after extensive desk research and multiple stakeholder interviews, that were used to identify partners, areas needing further development, challenges, blockers and collaboration opportunities. We designed a vision for next generation ERAs, initially focused on pesticides, based on the ideas of stakeholders and accounting for the identified strengths and weaknesses of the current ERA system. Workshops were held during which stakeholders were invited to comment on these draft concepts providing valuable feedback for further revision. The PERA vision is a visual framework for systems‐based ERA, with a concentric circle model. Its core circle builds upon and strengthens current ERA processes by focusing on pesticide specific aspects useful for comparability and decreasing the assessment complexity of pesticides. The inner core circle is surrounded by a supportive circle of landscape scale ERA, that addresses ecosystems properties of generic relevance for all pesticides. These two ERA circles are in turn connected to surrounding circles representing the agricultural, ecological and production systems as well as the political, economic and social systems. To fully optimize the process these circles need to be interconnected with information feed‐back loops. The vision and roadmap were designed to incorporate the strengths, knowledge and expertise of the current state into a new holistically framed systems‐based ERA. Strategies for transition, as well as concrete projects to spark the transition process are proposed and include concrete and tangible steps in a holistic direction within the current regulatory framework.